PENGARUH MODEL PROJECT BASED LEARNING DENGAN PENDEKATAN SAINTIFIK UNTUK MELATIHKAN KETERAMPILAN KOGNITIF TINGKAT TINGGI SISWA PADA MATA PELAJARAN IPA SDN GELAM 1 SIDOARJO - Mufidah, Lailatul; Jannah, Novaria Lailatul; Rahayu, Ika Putri; Setyawan, Zelika Jauza Bilqis (Primary School Teacher Education, Universitas Nahdlatul Ulama Sidoarjo, 2026)
Natural Science (IPA) learning in elementary schools is required not only to be oriented towards mastering concepts, but also to be able to train students' higher-order cognitive skills. However, science learning practices in elementary schools still tend to be teacher-centered so that they are not optimal in developing higher-order thinking skills. This study aims to determine the effect of implementing the Project Based Learning (PjBL) model with a scientific approach on higher-order cognitive skills in elementary school students' science subjects. This study uses a quantitative approach with a quasi-experimental research type and a pretest–posttest control group design. The research subjects consisted of two classes of students at Gelam 1 Elementary School, Sidoarjo, designated as the experimental class and the control class. The experimental class received learning using the Project Based Learning model with a scientific approach, while the control class used a scientific approach without PjBL. The research instrument was a science learning outcome test oriented to higher-order cognitive skills (C4–C6). Data were analyzed using descriptive statistics, prerequisite tests, and t-tests. The results showed that the average posttest score of the experimental class (82.10) was higher than the control class (71.30), with an increase in N-Gain of 0.62 in the experimental class and 0.36 in the control class. The t-test showed a significance value of 0.000 (p < 0.05), which indicated a significant difference between the two groups. Thus, it can be concluded that the application of the Project Based Learning model with a scientific approach is more effective in training students' high-level cognitive skills in science learning in elementary schools